The support of healthcare workers suffering from COVID 19. (1st June 2022) - Kacem, I.; Maoua, M.; Chouchane, A.; Kahloul, M.; Slama, Y.; Ajmi, M.; Naija, W.; Mrizak, N.
Abstract : Introduction: The COVID-19 pandemic has focused attention on the challenges and risks faced by frontline healthcare workers (HCW). Objectives: To describe the quality of management of HCW affected by the COVID-19. Methods: This is a cross-sectional study enrolling all HCW of Farhat Hached Academic hospital who had been affected by COVID-19 during the period from september to December 2020. Results: During the study period, 267 HCW were affected with a mean age of 42.3 ±10 years and a ratio-sex of 0.25. The most represented category was nurses (33.3%) followed by technicians (26.1%). Gynecology department had the highest number of affected HCW (14.4%).The majority of participants (97.4%) reported a medical care. Twelve HCW (4.5%) were hospitalized with an average length of hospital stay of 7.55 ± 6.12 days. The average length of sick leave was 18.68 ± 10.99 days. During the lockdown, 38.6% of HCW took care of their children without any external help. All of the HCW were supported by phone calls from colleagues in 88.4% of cases, the hierarchy in 67.4% of cases, occupational medicine in 60.3% of cases. Conclusions: The impact of COVID 19 is greater in HCW than in the general population. The affected staff should have a multidimensional management to avoid post covid sequelae in both physical and mental levels. Disclosure: No significant relationships.